Int Arch Clin Pharmacol 2019
DOI: 10.23937/2572-3987.1510019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Peripheral Trpm8 Ion Channel Activation on the Cardiovascular Parameters

Abstract: The role of TRP ion channels in the physiological processes is far from clear. In this work we studied the effect of the activation of the peripheral TRPM8 ion channel by its agonist menthol on the cardiovascular parameters in normotensive and hypertensive rats when animals were coming out of anesthesia. The role of the TRPM8 ion channel in the regulation of blood pressure was clearly seen in normotensive animals: Activation of this channel by application of 1% menthol (agonist of TRPM8 ion channel) to skin si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In the study of the impact of peripheral ion channel TRPM8 activation by menthol on some parameters of the cardiovascular system [ 20 ], a pronounced influence of this channel’s stimulation was detected that was aimed at increasing blood pressure in normotensive animals; in hypertensive animals, these responses were weaker. On the basis of those results and the data about decreased Trpm8 gene expression in hypertensive animals, the authors concluded that the downregulation of the TRPM8 ion channel may be a compensatory response aimed at preventing a blood pressure surge.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of the impact of peripheral ion channel TRPM8 activation by menthol on some parameters of the cardiovascular system [ 20 ], a pronounced influence of this channel’s stimulation was detected that was aimed at increasing blood pressure in normotensive animals; in hypertensive animals, these responses were weaker. On the basis of those results and the data about decreased Trpm8 gene expression in hypertensive animals, the authors concluded that the downregulation of the TRPM8 ion channel may be a compensatory response aimed at preventing a blood pressure surge.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to draw attention to the fact that our previous studies on the effect of activation of another cold-sensitive ion channel TRMP8 showed its opposite effect on blood pressure. Activation of the TRPM8 ion channel by its agonist menthol contributes to raising blood pressure [23]. Moreover, in hypertensive animals, the expression of the TRMP8 ion channel gene is reduced [24], which can be regarded as a compensatory change.…”
Section: Conflicts Of Interestmentioning
confidence: 99%